Leaf-Litter Mixtures Affect Breakdown and Macroinvertebrate Colonization Rates in a Stream Ecosystem - Abelho, Manuela (International Review of Hydrobiology, 2009)
Previous work in terrestrial and aquatic ecosystems has suggested that the relationship between breakdown rates of leaf litter and plant species richness may change unpredictability due to non-additive effects mediated by the presence of key-species. By using single- and mixed-species leaf bags (7 possible combinations of three litter species differing in toughness; common alder [Alnus glutinosa ], sweet chestnut [Castanea sativa ], and Spanish oak [Quercus ilex ilex ]), I tested whether leaf species diversity, measured as richness and composition, affects breakdown dynamics and macroinvertebrate colonization (abundance, richness and composition) during 90 days incubation in a stream. Decomposition rates were additive, i.e., observed decomposition rates were not different from expected ones. However, decomposition rates of individual leaf species were affected by the mixture, i.e., there were species-specific responses to mixing litter. The invertebrate communities colonizing the mixtures were not richer and more diverse in mixtures than in single-species leaf bags. On the opposite, mixing leaf species had a negative, non-additive effect on rates of shredder and taxa colonization and on macroinvertebrate diversity. (© 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
The following values have no corresponding Zotero field: publisher: WILEY-VCH Verlag
Keywords: Biodiversity; decomposition; FOREST; richness; shredders

Leaf-Litter Mixtures Affect Breakdown and Macroinvertebrate Colonization Rates in a Stream Ecosystem (International Review of Hydrobiology, 2009)
Previous work in terrestrial and aquatic ecosystems has suggested that the relationship between breakdown rates of leaf litter and plant species richness may change unpredictability due to non-additive effects mediated by the presence of key-species. By using single- and mixed-species leaf bags (7 possible combinations of three litter species differing in toughness; common alder [Alnus glutinosa ], sweet chestnut [Castanea sativa ], and Spanish oak [Quercus ilex ilex ]), I tested whether leaf species diversity, measured as richness and composition, affects breakdown dynamics and macroinvertebrate colonization (abundance, richness and composition) during 90 days incubation in a stream. Decomposition rates were additive, i.e., observed decomposition rates were not different from expected ones. However, decomposition rates of individual leaf species were affected by the mixture, i.e., there were species-specific responses to mixing litter. The invertebrate communities colonizing the mixtures were not richer and more diverse in mixtures than in single-species leaf bags. On the opposite, mixing leaf species had a negative, non-additive effect on rates of shredder and taxa colonization and on macroinvertebrate diversity. (© 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Effects of Leaf Litter Species on Macroinvertebrate Colonization during Decomposition in a Portuguese Stream - Abelho, Manuela (International Review of Hydrobiology, 2008)
This study evaluated if there are differences in leaf breakdown and invertebrate colonization among tree species differing in quality (toughness), and which factors could influence these differences. Common alder leaves decomposed significantly faster then either sweet chestnut or Spanish oak (k values of –0.0332, –0.0108, and –0.0112, respectively) during the first 2 months. Shredder abundance was highest when leaf mass remaining was 50%, and the samples clustered in mixed groups of sampling dates and leaf species, suggesting that stage of decomposition was an important factor influencing shredder colonization. During the first two months of decomposition, the physicochemical characteristics of leaf litter and the interaction between leaf toughness and the occurrence of frequent spates seemed to be the main factors affecting leaf breakdown rates in the stream. (© 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
The following values have no corresponding Zotero field: publisher: WILEY-VCH Verlag
Keywords: breakdown; colonisation; leaves; river; shredders

Effects of Leaf Litter Species on Macroinvertebrate Colonization during Decomposition in a Portuguese Stream (International Review of Hydrobiology, 2008)
This study evaluated if there are differences in leaf breakdown and invertebrate colonization among tree species differing in quality (toughness), and which factors could influence these differences. Common alder leaves decomposed significantly faster then either sweet chestnut or Spanish oak (k values of –0.0332, –0.0108, and –0.0112, respectively) during the first 2 months. Shredder abundance was highest when leaf mass remaining was 50%, and the samples clustered in mixed groups of sampling dates and leaf species, suggesting that stage of decomposition was an important factor influencing shredder colonization. During the first two months of decomposition, the physicochemical characteristics of leaf litter and the interaction between leaf toughness and the occurrence of frequent spates seemed to be the main factors affecting leaf breakdown rates in the stream. (© 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)